Patterns and Tidal Characteristics of East Coast of Bintan Island, Riau Archipelago Province - Mario Putra Suhana; I Wayan Nurjaya; Nyoman Metta N. Natih (Politeknik Negeri Batam, 2018)
Tide is one of the important factors that affect the oceanographic processes around widely as waters flow. Tides also give significant effects against the dynamic of coastal area. This research was conducted considering the importance roles of tides data against all oceanographic phenomenon that gives the effects on activities around the area of coastal waters. This research was conducted around the area of east coast of Bintan Island Riau Archipelago Province in December 2017. Tidal data is retrieved from the global tidal modelling uses MIKE 21. The results of the analysis show the range of tidal height on the east coast of Bintan Island during 2007-2017 is 0.70-3.50 m of height range with the average of mean sea level (MSL) is 2.20-2.60 m. Generally, tidal fluctuations on east coast of Bintan Island form an asymmetric pattern which is a common pattern occurring in any waters. The tidal type of the east coast of Bintan Island is mixed predominantly semi diurnal with the value of formzahl number in each station respectively is 1.19-1.44. The interesting phenomenon obtained from this research is during 2007-2017 the maximum of sea level height in each station tends to decrease, this is considered attractive because over the past 20 years earth surface temperature have tended to increase so that melting of ice in polar has implications for increasing of sea water volume. Keywords: Tide, harmonics component, oceanography, east coast of Bintan Island